2020
DOI: 10.1126/science.aay2002
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral 3C protease activates the human NLRP1 inflammasome in airway epithelia

Abstract: Immune sensor proteins are critical to the function of the human innate immune system. The full repertoire of cognate triggers for human immune sensors is not fully understood. Here, we report that human NLRP1 is activated by 3C proteases (3Cpros) of enteroviruses, such as human rhinovirus (HRV). 3Cpros directly cleave human NLRP1 at a single site between Glu130 and Gly131. This cleavage triggers N-glycine–mediated degradation of the autoinhibitory NLRP1 N-terminal fragment via the cullinZER1/ZYG11B complex, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
150
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 56 publications
5
150
1
Order By: Relevance
“…1,3 ). This unique mechanism involving 'functional degradation' is conserved in the activation of human NLRP1 (hNLRP1) by the 3C proteases of enteroviruses 14 and in the activation of CARD8 by HIV-1 protease 15 .…”
mentioning
confidence: 99%
“…1,3 ). This unique mechanism involving 'functional degradation' is conserved in the activation of human NLRP1 (hNLRP1) by the 3C proteases of enteroviruses 14 and in the activation of CARD8 by HIV-1 protease 15 .…”
mentioning
confidence: 99%
“…Human nucleotide-binding domain leucine-rich repeat pyrin domain-containing 1 (hNLRP1) was the first PRR discovered to form an inflammasome (Martinon et al, 2002), but the danger signal that activates hNLRP1 has eluded identification for nearly 20 years. Two recent studies provide evidence that hNLRP1 directly senses (at least) two extraordinarily different things: enteroviral 3C protease activity (Robinson et al, 2020) and long double-stranded RNA (dsRNA) (Bauernfried et al, 2020).…”
mentioning
confidence: 99%
“…For example, CARD8 and NLRP1 may have evolved to respond to different pathogens. Consistent with this idea, recent reports revealed that human rhinovirus 3C protease and HIV protease directly cleave and activate human NLRP1 and CARD8, respectively (Robinson et al, 2020;Tsu et al, 2020;Wang et al, 2020). Moreover, human NLRP1 was also recently reported to sense intracellular long doublestranded RNAs by directly binding them through its leucine-rich repeat (LRR) domain (Bauernfried et al, 2020), which is absent in CARD8.…”
Section: Discussionmentioning
confidence: 72%
“…The inflammatory CT must be released from the repressive NT for CARD8 activation (Johnson et al, 2018). DPP8/9 inhibitors, including VbP, activate the CARD8 inflammasome in human macrophages and resting lymphocytes and the NLRP1 inflammasome in skin and airway epithelial cells (Johnson et al, 2020;Johnson et al, 2018;Linder et al, 2020;Robinson et al, 2020;Zhong et al, 2018). The mechanisms of DPP8/9 inhibitor-induced CARD8 and NLRP1 inflammasome activation have not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%